Alcohol consumption and lung cancer risk in never smokers: a pooled analysis of case-control studies. (13th November 2017) - García Lavandeira, José A; Ruano-Ravina, Alberto; Kelsey, Karl T; Torres-Durán, María; Parente-Lamelas, Isaura; Leiro-Fernández, Virginia; Zapata, Maruxa; Abal-Arca, José; Vidal-García, Iria; Montero-Martínez, Carmen; Amenedo, Margarita; Castro-Añón, Olalla; et al.
Abstract: Background: Lung cancer is the deadliest cancer in developed countries but the etiology of lung cancer risk in never smokers (LCRINS) is largely unknown. We aim to assess the effects of alcohol consumption, in its different forms, on LCRINS. Methods: We pooled six multi-center case-control studies developed in the northwest of Spain. Cases and controls groups were composed of never smokers. We selected incident cases with anatomopathologically confirmed lung cancer diagnoses. All participants were personally interviewed. We performed two groups of statistical models, applying unconditional logistic regression with generalized additive models. One considered the effect of alcohol type consumption and the other considered the quantity of each alcoholic beverage consumed. Results: A total of 438 cases and 863 controls were included. Median age was 71 and 66, years, respectively. Adenocarcinoma was the predominant histological type, comprising 66% of all cases. We found that any type of wine consumption posed an OR of 2.20 OR 95%CI 1.12—4.35), and spirits consumption had an OR of 1.90 (95%CI 1.13—3.23). Beer consumption had an OR of 1.33 (95%CI 0.82–2.14). These results were similar when women were analyzed separately, but for men there was no apparent risk for any alcoholic beverage. The dose-response analysis for each alcoholic beverage revealed no clear pattern. Conclusions: Wine and spirits consumption might increase the risk of LCRINSs, particularly in females. These results have to be taken with caution given the limitations of the present study.